The Dark Side of Digital Consumption: A Phenomenological Study of Consumer Anxiety Over Fear of Missing Out (FOMO) in Impulsive Purchasing Behaviour in Response to Digital Advertising - Rundika Pratiwi, Endah (Asosiasi Ahli Administrasi Indonesia, 2026)
Digital consumption is now an important part of everyday life, and it has significant emotional and psychological effects on users. The purpose of this study is to explore consumers' subjective experiences with social media advertising pressure, particularly in relation to the phenomena of anxiety and Fear of Missing Out (FOMO), which drive impulsive purchasing behaviour. This study focuses on the depth of individual experiences when exposed to powerful advertising algorithms. This is done using a qualitative phenomenological approach. The results show that digital advertising on social media presents an ideal lifestyle that creates constant social pressure rather than simply marketing messages. The fear of being left behind by trends or other people's experiences (FOMO) is a cause of consumer anxiety, which drives them to make impulsive purchases. The results indicate that digital consumption behaviour is more influenced by communicative experiences and social constructs than by rational economic actions. Theoretically, this study enriches marketing communication research by providing a critical perspective on the dark side of digital consumption through a phenomenological lens.